Frontispiece: Appending Diverse π‐Extended Acceptors with Tetrathiafulvalene/Dithiafulvalene Donors: Multistate Redox Properties, Radical Ion Generation, and Mid‐IR‐Absorbing Mixed‐Valence States. Issue 8 (6th February 2018) - Keshri, Sudhir Kumar; Asthana, Deepak; Chorol, Sonam; Kumar, Yogendra; Mukhopadhyay, Pritam
Abstract : New π‐extended systems with attractive opto‐electronic properties were realized, in which the anhydride/imide‐based acceptors (A) and the number of tetrathiafulvalene (TTF)/dithiafulvalene (DTF) donors (D) were altered. Large π‐rings like benzoperylene and coronene were integrated for the first time. Furthermore, a new class of radical cations (D .+ ) and radical anions (A .− ) were also obtained under ambient conditions. Intriguingly, mixed‐valence states with absorption in the mid‐infrared (MIR) region could be established. For more information, see the Full Paper by P. Mukhopadhyay et al. onpage 1821 ff.